Combining economic and political development : the experience of MENA - Luciani, Giacomo, 1948- (International development policy., 2017)
Since 2011, democratic transitions in the Middle East and North Africa have mostly failed to consolidate and have been hindered by the difficult economic heritage of previous authoritarian governments. Yet newly established democratic governments must deliver on the expectations of their people, especially the poorer strata, otherwise disillusionment may open the door to restoration of authoritarian rule. Can democracy succeed? Various ideas for economic policies that may help consolidate the early democratisation process are proposed in this volume, while major obstacles on the way to democratic success are also highlighted.